2015
DOI: 10.1080/10916466.2014.968285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of the Riser in the Fluid Catalytic Cracking Process

Abstract: In a 3D model simulating in the riser of the fluid catalytic cracking (FCC) was studied feedstock conversion and yield products. Computational fluid dynamics (CFD) and Eulerian-Eulerian approach with a 12-lump model was used to predict the hydrodynamic and kinetic behavior, respectively. All the equations and conditions were solved using a solver Ansys CFX 14.0. The different operation variables and hydrodynamic effects of the riser are evaluated. Predictions from the model are shown and comparison with experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…[ 1–3 ] Furthermore, with the improvement in computational performance since the 2000s, there has been an increase in the reports of complex analyses, such as a large number of lumps, parameters related to catalyst deactivation, and risers' and cyclones' performance with computational fluid dynamics (CFD). For example, Bollas et al studied five Lump models and catalyst deactivation; [ 4 ] Yakubu et al studied six‐Lump models and reaction analysis in risers; [ 5 ] Alvarez‐Castro et al studied twelve Lump models and riser analysis using numerical software; [ 6 ] Olafadehan et al reported a riser study using the numerical computation software MATLAB; and Yang et at. reported one using EQUATRAN‐G.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Furthermore, with the improvement in computational performance since the 2000s, there has been an increase in the reports of complex analyses, such as a large number of lumps, parameters related to catalyst deactivation, and risers' and cyclones' performance with computational fluid dynamics (CFD). For example, Bollas et al studied five Lump models and catalyst deactivation; [ 4 ] Yakubu et al studied six‐Lump models and reaction analysis in risers; [ 5 ] Alvarez‐Castro et al studied twelve Lump models and riser analysis using numerical software; [ 6 ] Olafadehan et al reported a riser study using the numerical computation software MATLAB; and Yang et at. reported one using EQUATRAN‐G.…”
Section: Introductionmentioning
confidence: 99%
“…Essas reações são indesejáveis, pois reduzem a eficiência do processo por aumentar o rendimento do coque, além de gerar produtos de qualidade inferior aos produtos gerados pelo craqueamento catalítico. Portanto, é de grande importância investigar parâmetros do processo que podem ser modificados para amenizar esses fenômenos indesejados (ALVAREZ-CASTRO et al, 2012;BARBOSA, 2012).…”
Section: Leito Fluidizado Gás-sólidounclassified